124 Post-operative mortality and risk of COVID-19 in patients receiving urgent elective surgical care at a COVID clean facility during the COVID 19 pandemic: a cross-sectional study. (4th May 2021) - Cheung, Lok Ka; Shaikh, Shafaque; Rai, Shanju; Lawrie, David; Qadir, Abdul
Abstract: Introduction: The Sars-Cov2 related COVID-19 pandemic has triggered the adoption of unprecedented approaches to contain it across the globe at a very short notice. The aim of this study is to determine post-operative mortality and the risk of developing COVID-19 in a COVID-19 negative population undergoing elective surgical care in a COVID-clean facility. We also explored patient experiences and satisfaction as well patient reported post-operative COVID related symptoms through a patient satisfaction survey. Method: A patient satisfaction survey was built into the service which was performed by means of a telephone follow-up at 30 days from procedure. One of the aspects of the service review was to capture data on patients developing COVID-19 symptoms post-operatively but not requiring hospital admission or testing. Results & Conclusion: Our study has shown promising results with the early outcomes of elective surgical care delivered through a COVID-clean facility with no mortality, low morbidity and high patient satisfaction across all 5 specialties (Plastic surgery, Urology, Gynaecology, General Surgery) in 455 patients operated on over 10 weeks. We have demonstrated safe delivery of elective surgical services by utilising a COVID-clean facility minimising the negative impact of delays experienced due to the COVID-19 pandemic.